Coordinated Changes in Antioxidative Enzymes Protect the Photosynthetic Machinery from Salinity Induced Oxidative Damage and Confer Salt Tolerance in an Extreme Halophyte Salvadora persica L. - Rangani, Jaykumar; Parida, Asish K.; Panda, Ashok; Kumari, Asha (Frontiers in Plant Science, 2016)
Salinity-induced modulations in growth, photosynthetic pigments, relative water content, lipid peroxidation, photosynthesis, photosystem II efficiency and changes in activity of various antioxidative enzymes were studied in the halophyte S. persica treated with various levels of salinity (0, 250, 500, 750 and 1000 mM NaCl) to obtain an insight into the salt tolerance ability of this halophyte. Both fresh and dry biomass as well as leaf area declined at all levels of salinity whereas salinity caused an increase in leaf succulence. A gradual increase was observed in the Na+ content of leaf with increasing salt concentration up to 750 mM NaCl, but at higher salt concentration (1000 mM NaCl), the Na+ content surprisingly dropped down to the level of 250 mM NaCl. The chlorophyll and carotenoid contents of the leaf remained unaffected by salinity. The photosynthetic rate (PN), stomatal conductance (gs), the transpiration rate (E), quantum yield of PSII (ΦPSII), photochemical quenching (qP) and electron transport rate (ETR) remained unchanged at low salinity (250 to 500 mM NaCl) whereas, significant reduction in these parameters were observed at high salinity (750 to 1000 mM NaCl). The relative water content (RWC %) and water use efficiency (WUE) of leaf remained unaffected by salinity. The salinity had no effect on maximum quantum efficiency of PS II (Fv/Fm) which indicates that PS II is not perturbed by salinity-induced oxidative damage. Analysis of the isoforms of antioxidative enzymes revealed that the leaves of S. persica have two isoforms each of Mn-SOD and Fe-SOD and one isoform of Cu-Zn SOD, three isoforms of POX, two isoforms of APX and one isoform of CAT. There was differential responses in activity and expression of different isoforms of various antioxidative enzymes. The malondialdehyde (MDA) content (a product of lipid peroxidation) of leaf remained unchanged in S. persica treated with various levels of salinity. Our results suggest that the absence of pigment degradation, the reduction of water loss and the maintenance of water use efficiency and protection of PSII from salinity-induced oxidative damage by the coordinated changes in antioxidative enzymes are important factors responsible for salt tolerance of S. persica.